Hypoxia-Induced Modulation of OCT-4, SOX-2, NANOG, and KLF-4 Expression in Mesenchymal Stem Cells - Irawan, Risky Chandra Satria; Hidayah, Nurul; Wilaksono, Bhirau (Stem Cell and Cancer Research (SCCR), 2024)
Background: Mesenchymal stem cells (MSCs) possess remarkable regenerative and immunomodulatory capabilities, largely attributed to their intrinsic stemness properties regulated by transcription factors such as OCT-4, SOX-2, NANOG, and KLF-4. However, in vitro culture under normoxia often leads to stemness decline. Hypoxic preconditioning has been proposed to preserve stemness, though the optimal duration of exposure remains unclear. This study aimed to evaluate the time-dependent effects of hypoxia on the expression of core stemness-related transcription factors in human umbilical cord Wharton’s jelly-derived MSCs. Methods: MSCs (passage 5) obtained from the Stem Cell and Cancer Research (SCCR) Laboratory were cultured under hypoxia (5% O₂) for 0, 4, 6, 10, 12, and 24 hours. Gene expression of OCT-4, SOX-2, NANOG, and KLF-4 was quantified by qRT-PCR using GAPDH as a reference. Morphological changes were observed via phase-contrast microscopy. Statistical analysis was performed using one-way ANOVA with Tukey’s post hoc test. Results: Hypoxic exposure induced a significant, time-dependent upregulation of OCT-4, SOX-2, and NANOG, with peak expression at 12 hours (approximately 13-, 7-, and 5-fold increases, respectively; p < 0.05). KLF-4 expression showed a modest elevation but was not statistically significant. Prolonged hypoxia (24 hours) resulted in a marked decline in all gene expressions toward baseline levels, accompanied by cell rounding and detachment. These findings indicate that short-term hypoxia enhances MSC stemness, while extended exposure triggers stress-related responses. Conclusion: Controlled short-term hypoxia (approximately 12 hours at 5% O₂) optimally enhances MSC stemness gene expression without compromising morphology or viability. This duration represents an effective preconditioning window for maintaining MSC multipotency and may improve the consistency and therapeutic efficacy of MSC-based applications.